Body Fat Distribution and Anthropometric Correlates of Primary School Children in Ilorin Nigeria (Western Journal of Medical and Biomedical Sciences, 2023)
Body fats in children determines the nutritional status as well as predict the risk of long-term occurrences of noncommunicable diseases such as obesity and type II diabetes mellitus. The body fat changes are mainly influenced by age, sex, genetics and ethnic background. This study describes the body fat distribution of children in the pre-adolescent / early adolescent period in the black ethnic group and their nutritional status using both the direct and indirect methods of body fat measurements. A cross-sectional survey was carried out among 568 public and private primary school children aged between 6-12 years in Ilorin metropolis. Body fat was measured by bio-impedance using Segmental Body Composition Analyzer. Weight and height were measured using a standardized beam balance with an attached stadiometer. Data was analyzed using SPSS v 23. Mean (+SD) of continuous variables were determined. Two means were compared using t test while mean greater than two were compared using ANOVA. Significant p value was < 0.05. The Mean body fat was highest in the age group 8 – 9 years with a statistically significant difference across the age group (p < 0.001). Females had a higher mean body fatwhile private school pupils had a higher body fat than their publicschool counterparts(p < 0.001).The overall mean waist and hip circumference was higher among pupils aged ≥ 10 years (p ˂ 0.001). There was significant positive correlation between Age, BMI and waist circumference with body fat (p = 0.001).There was a generally low mean BMI for age(
Keywords: Anthropometric; Body fat; BMI; Correlates; Hip; Waist circumference; Pre-adolescent